3D Organisation of Cells in Pseudostratified Epithelia - Iber, Dagmar; Vetter, Roman (Frontiers in Physics, 2022)
Pseudostratified epithelia have smooth apical and basal surfaces, yet along the apical-basal axis, cells assume highly irregular shapes, which we introduce as punakoids. They interact dynamically with many more cells than visible at the surface. Here, we review a recently developed new perspective on epithelial cell organisation. Seemingly random at first sight, the cell packing configurations along the entire apical-basal axis follow fundamental geometrical relationships, which minimise the lateral cell-cell contact energy for a given cross-sectional cell area variability. The complex 3D cell neighbour relationships in pseudostratified epithelia thus emerge from a simple physical principle. This paves the way for the development of data-driven 3D simulation frameworks that will be invaluable in the simulation of epithelial dynamics in development and disease.